The species of the Hypostomus cochliodon group (Siluriformes: Loricariidae) - Armbruster, Jonathan W. (Zootaxa, 2003)
The Hypostomus cochliodon group consists of eight species that were formerly recognized as Cochliodon Kner: H. cochliodon Kner, H. hondae (Regan), H. levis (Pearson), H. oculeus (Fowler), H. plecostomoides (Eigenmann), H. pospisili (Schultz; a synonym of H. hondae), H. pyrineusi (Miranda-Ribeiro), and H. taphorni (Lilyestrom) and four additional species described herein: H. ericius, H. hemicochliodon, H. pagei, and H. sculpodon. The species occur in four phenetic groups: the intermediate group of H. hemicochliodon and H. sculpodon that appear to be transitional species between other Hypostomus and the H. cochliodon group in terms of diet and tooth shape, a monotypic group containing H. cochliodon, a group characterized by an odontodeless opercle that contains H. ericius, H. levis, H. oculeus, H. pyrineusi, and H. taphorni, and an undifferentiated northern group that contains H. hondae, H. pagei, and H. plecostomoides.